Gene disruption by transformation in Neurospora crassa. - Paietta, J V (1985)
To establish conditions which might permit deliberate gene disruptions in Neurospora crassa, we studied transformation with linear DNA fragments. The transformation frequency observed was increased about twofold in comparison with that obtained with circular plasmid DNA. However, only a low proportion, approximately 10%, of the integration events occurred at the homologous site, whereas most integrations of transforming DNA took place in nonhomologous regions. It was also found that multiple integration events frequently occurred in individual transformants. A plasmid, designated pJP12, was constructed that contains the N. crassa am+ gene interrupted by insertion into its coding region of a DNA segment carrying a functional Neurospora qa-2+ gene. A fragment of Neurospora DNA that contains this am qa-2+ construction was obtained from plasmid pJP12 and used to transform an am+ qa-2 strain in an attempt to disrupt the resident am+ gene. After the initial qa-2+ transformants were converted to homokaryons by appropriate crosses, 10 independent transformants with an am mutant phenotype were found among 117 examined. Each of these qa-2+ am transformants showed the loss of a hybridization band in Southern blots of genomic DNA that corresponded to the normal am+ gene and the presence of a new hybridization band, consistent with an alteration in the am+ region.